2011
DOI: 10.1177/2041297510393627
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element modelling of a novel flanging process on a cylinder with a large diameter–thickness ratio

Abstract: To solve existing problems of current processing methods for flanged cylinders with a large diameter-thickness ratio, a double-roller clamping spinning (DRCS) process is proposed as a novel flanging process on a cylinder. Finite-element (FE) numerical simulation is used to research the DRCS process. First, on the basis of non-linear FE analysis software Abaqus/ Explicit, an FE model for the DRCS process is established. Second, some key problems in FE modelling of DRCS are solved, for example, the definition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The 180° and 270° direction wall thickness was the largest, while the smallest appeared in the 0° and 90° direction. The distribution pattern of the wall thickness was consistent with that reported in Fan et al 17 The reason for this phenomenon is that the material thinned and displaced in the direction opposite to the motion of the roller (backward tube spinning), since the rotating was through 180°. Hence, wall thickness was greater in the region from 180° to 270°, when compared to that from 0° to 90°.…”
Section: Simulation Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The 180° and 270° direction wall thickness was the largest, while the smallest appeared in the 0° and 90° direction. The distribution pattern of the wall thickness was consistent with that reported in Fan et al 17 The reason for this phenomenon is that the material thinned and displaced in the direction opposite to the motion of the roller (backward tube spinning), since the rotating was through 180°. Hence, wall thickness was greater in the region from 180° to 270°, when compared to that from 0° to 90°.…”
Section: Simulation Results and Discussionsupporting
confidence: 89%
“…It can be observed that the design of the roller path plays a decisive role for parts with complex geometric features. A novel flanging process on a cylinder with a large diameter-thickness ratio was simulated by Fan et al 17 through FEM. Xiao et al 18 studied the non-axisymmetric multi-pass rotation characteristics of the oblique flange cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Total procedure of forming the tube into dome is simulated. Generally, researchers like Fan et al, 15 Huang et al, 12 and Lexian and Dariani 10 have used shell elements to model spinning processes because of long computation times of the models with solid elements. In this study, cubic solid elements are used to preserve the stress and strain variation in thickness.…”
Section: Fe Simulationmentioning
confidence: 99%
“…The process is categorized as one of the various spinning procedures in which there is no mandrel or die. Some recent articles on general spinning and flow forming processes include the works of Razani et al 1 on the experimental study of flow forming of steel tubes, Wang et al 2 on the study of the effect of roller feed on wrinkling in conventional spinning and works of Fan et al 3 on the investigation of a novel flanging method by spinning.…”
Section: Introductionmentioning
confidence: 99%